anonymous
  • anonymous
Solve the system of equations using the elimination method. 3x-4y=0 2x-3y=-1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
how do i solve this?
anonymous
  • anonymous
multiply the first equation by 2 and the 2nd equation by -3 and add them together
anonymous
  • anonymous
2(3x-4y=0) => 6x-8y=0 -3(2x-3y=-1)=>-6x+9y=3 adding them together give you y=3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
6x-8y=0-eqn1 6x-9y=-3-eqn2 eqn1-eqn2=>y=3 6x-24=0 6x=24 x=4
anonymous
  • anonymous
okay. got iy.
campbell_st
  • campbell_st
Label the equations 3x - 4y = 0 (1) and 2x - 3y = -1 (2) the 2 x (1) - 3 x (2) this will eliminate x as shown below 6x - 8y = 0 -6x+ 9y = -3 y = -3 hence y = -3 and sub into either equation to find x, x = 4
campbell_st
  • campbell_st
oops y = 3
anonymous
  • anonymous
okay. thanks you guys! i really appreciate it! :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.